Towards an interpretation of the Portuguese cultural tourist: Motivations and constraints - Ramires, Ana; Monteiro, Anabela; Lopes, Sofia; Rodrigues de Sousa , Sara; Leite , Ângela (Turyzm/Tourism, 2022)
The importance of cultural tourism for the development of tourist destinations has created a need for knowledge on both supply and demand sides, related to the motivations and constraints which can affect the decisions of the cultural tourist. The aim of this study is to develop and validate for the Portuguese tourists two scales to measure motivations to travel and its constraints, considering theories of needs and constraints, and to examine differences according to tourists’ socio-demographic characteristics. The scales were determined using a non-linear principal component analysis followed by bootstrap confirmatory factor analysis, and differences were examined using parametric tests. A six-dimensional model for motivations and a five-dimensional model for constraints were validated, both with good overall fit. Motives linked to culture, intellectual curiosity and cultural knowledge stand out with high levels of relevance. Lack of resources and other commitments are the most important constraints. Significant differences were found in almost all characteristics. The results reveal influential dimensions on travel decisions which are of utmost importance for the design of the cultural offer of destinations.